The role of biochar in ameliorating disturbed soils and sequestering soil carbon in tropical agricultural production systems - Mekuria, Wolde; Noble, A.D. (Hindawi Limited, 2013)
Agricultural soils in the tropics have undergone significant declines in their native carbon stock through the long-term use of extractive farming practices. However, these soils have significant capacity to sequester CO2 through the implementation of improved land management practices. This paper reviews the published and grey literature related to the influence of improved land management practices on soil carbon stock in the tropics. The review suggests that the implementation of improved land management practices such as crop rotation, no-till, cover crops, mulches, compost, or manure can be effective in enhancing soil organic carbon pool and agricultural productivity in the tropics. The benefits of such amendments were, however, often short lived, and the added organic matters were usually mineralized to CO2 within a few cropping seasons leading to large-scale leakage. We found that management of black carbon (C), increasingly referred to as biochar, may overcome some of those limitations and provide an additional soil management option. Under present circumstances, recommended crop and land management practices are inappropriate for the vast majority of resource constrained smallholder farmers and farming systems. We argue that expanding the use of biochar in agricultural lands would be important for sequestering atmospheric CO2 and mitigating climate change, while implementing the recommended crop and land management practices in selected areas where the smallholder farmers are not resource constrained.